2014
DOI: 10.1371/journal.pone.0111324
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane-Derived Mesenchymal Cells and Their Conditioned Media: Potential Candidates for Uterine Regenerative Therapy in the Horse

Abstract: Amniotic membrane-derived mesenchymal cells (AMCs) are considered suitable candidates for a variety of cell-based applications. In view of cell therapy application in uterine pathologies, we studied AMCs in comparison to cells isolated from the endometrium of mares at diestrus (EDCs) being the endometrium during diestrus and early pregnancy similar from a hormonal standpoint. In particular, we demonstrated that amnion tissue fragments (AM) shares the same transcriptional profile with endometrial tissue fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…A detailed characterization of these cells was performed in the paper of Corradetti et al [39]. In this study, a molecular characterization of EDCs was performed only at passage (P)0 as a de facto control for gene expression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed characterization of these cells was performed in the paper of Corradetti et al [39]. In this study, a molecular characterization of EDCs was performed only at passage (P)0 as a de facto control for gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…After isolation from endometrial tissue, cells were analyzed to detect the expression of specific endometrial genes as previously reported [39]. Total RNA was extracted from endometrial cells immediately after isolation (P0) using TRI Reagent Solution (Life Technologies, Monza, Italy) and conventional RT-PCR was performed with RBC Taq DNA Polymerase (RBC Bioscience) using previously optimized primers [39].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation rate was determined in triplicate on AD-, BM-, and CBF-MSCs as previously reported [46,47]. Doubling time was assessed from P1 to P10 in normoxic and hypoxic conditions to determine the effect of lowtension oxygen on cell proliferation.…”
Section: Proliferation Assays (Doubling Time) In Normoxic and Hypoxicmentioning
confidence: 99%
“…They have been proven effective in endometrial cell replenishment when low proliferation is associated to pregnancy failure in vitro [24] and to be sufficient to stimulate the structural and functional regeneration of cardiac [25,26], renal [27,28], tendon [29], and spinal cord [30] tissues Figure 1 summarizes the MSC features that make them a powerful tool for therapeutic purposes.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%